Assessing banks efficiency: DEA implementation - Milica Inđić; Aleksandra Marcikić Horvat; Milos Pjanić (BizInfo)
By examining intermediate, operating, and profitability aspects, this paper aims to construct a performance model for evaluating the relative efficiency and potential for improvement of 20 banks operating in Serbia for the 2022-2023 period. Data Envelopment Analysis (DEA), which belongs to relatively new data-oriented techniques, was used in the research to measure efficiency. To achieve its goals, the paper makes use of the CCR and BCC, two fundamental DEA models, and three approaches: intermediary, operating and profitability. The results of the analysis showed that the highest efficiency can be attributed o the use of the intermediate approach, while the lowest efficiency of banks can be attributed to the profitability approach. Additionally, the BCC model has higher efficiency compared to the CCR model. According to the analysis results, efficiency has generally grown and is comparatively stable.